NEO-INSTITUTIONALISM AS METHODOLOGY OF ANALYSIS INFORMAL INSTITUTION OF POLITICS - Попазогло, В. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The research potential of neo-institutionalism as a methodology for analyzing informal political institutions is analyzed. It is emphasized that in the system of informal political institutions there are not only destructive but also constructive institutions. It is emphasized that most informal institutes appear as a result of uncontrolled social processes; their appearance largely depends on rooted social practices. Political corruption, nepotism, patronage, etc. attributed to destructive informal institutions. The essence of such political institutions from the standpoint of neo-institutionalism is explored. The differences in the understanding of the political institutions in the interpretation of institutionalism and neo-institutionalism are emphasized. It is proved that neo-institutionalism is a step forward in analyzing the essence of a political institution. He departed from the conservatism of traditional institutionalism, which under the political institutions was understood by state institutions, political organizations. It is noted that the specificity of neo-institutionalism consists in the fact that political institutions are understood through the prism of the interrelations of formal norms and informal rules of the game. It is pointed out that destructive informal institutions are examples of latent policy. They change, weaken or ruin the rules underlying the formal institutions. It is emphasized that most of the destabilizing processes for the state and society have a source of their own origin, namely, informal institutional space.